Risk Prediction Questionnaire and Item Screening for Acute Exacerbation of Asthma Based on the Modified Delphi Technique - YANG Jiang, WANG Minghang, LI Jiansheng, LIN Xiaohong, LIU Yuanyuan, XIE Yang, LI Suyun (Zhongguo quanke yixue, 2022)
Background China owns a huge number of asthma patients and an increasing incidence of asthma, but low rate of overall control and high rate of acute asthma exacerbation. Moreover, there is a lack of methods for systematically screening the risks of acute exacerbation of asthma. Objective To develop a risk prediction questionnaire for acute exacerbation of asthma after screening the associated risk factors using the modified Delphi technique, providing a reference for building a multidimensional risk prediction model of asthma acute exacerbation. Methods Based on literature reports and our clinical pre-investigation results, an expert consultation questionnaire on risk predictors of acute exacerbation of asthma was developed, and was distributed through E-mail to 30 experts for review through two rounds of online consultation survey using the modified Delphi technique conducted from April to October 2021. SPSS 25.0 was used to assign weight and analyze the risk predictors. Then according to the screening criteria developed by the experts, the risk predictors were finally determined. Results Both two rounds of consultation achieved a 100% response rate. The familiarity, judgment, and authority coefficients as well as Kendall's W were 0.894, 0.963, 0.929, and 0.331, respectively, for the first round of expert consultation (P<0.001) , and were 0.920, 0.976, 0.948, and 0.437, respectively, for the second round of expert consultation (P<0.001) . The determined risk predictors of acute exacerbation of asthma include six domains (clinical symptoms and signs, conditions, quality of life, biological information, traditional Chinese medicine syndromes and basic demographics) , and 29 indices including severity of asthma, Asthma Control Test, wheezing, chest tightness, allergy history, hormone therapy, work and living environment, eosinophils, number of exacerbations in the past year, treatment compliance, climate and seasonal changes, and so on. Conclusion The based on the modified Delphi method, the risk predictors of acute exacerbation of asthma determined using expert consultation with the modified Delphi technique include the aforementioned six domains and 29 indices, which is relatively concise, and can provide a reference for follow-up studies.